PENGARUH REGULATORY PRESSURE, ENVIRONMENTALLY FRIENDLY INNOVATION, DAN DEMAND FOR ENVIRONMENTALLY FRIENDLY PRODUCTS TERHADAP DAYA SAING SERTA KINERJA BISNIS BERKELANJUTAN PADA UMKM DI INDONESIA - Sukma Umbara tirta Firdaus; Adriana Pakendek; Robiatun Sifa Innisa; Diah Khairunnisa; Wildatun Alifiana Putri; Zainurrafiqi Zainurrafiqi (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the impact of regulatory pressure, eco-innovation, and eco-friendly product demand on the competitiveness and sustainable business performance of MSMEs in Indonesia, specifically in the Sampang and Pamekasan districts. The study focuses on how these factors interact to enhance sustainable business outcomes.A quantitative approach was employed using a structured survey questionnaire, which was distributed to 495 MSME managers in Sampang and Pamekasan. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to assess the direct and indirect relationships among the variables.The findings reveal that regulatory pressure, eco-innovation, and eco-friendly product demand all significantly influence the sustainable business performance of MSMEs. Additionally, sustainable competitive advantage was found to mediate the relationship between these factors and business performance, underscoring its role in facilitating long-term business success. This study contributes new insights into the dynamic interactions between environmental regulations and market demands in shaping MSME performance.The study fills a gap in the literature by integrating regulatory pressure, eco-innovation, and eco-friendly product demand within a sustainable competitive advantage framework, offering a fresh perspective on MSME sustainability in Indonesia.This research provides practical implications for policymakers and business owners aiming to enhance MSME competitiveness through green innovation and regulatory compliance. Future research could explore additional mediating variables, such as corporate culture or external partnerships, to further understand MSME sustainability dynamics.